A Protective Role of Glibenclamide in Inflammation-Associated Injury - Gensheng Zhang; Xiuhui Lin; Shufang Zhang; Huiqing Xiu; Chuli Pan; Wei Cui (Hindawi Limited, 2017)
Glibenclamide is the most widely used sulfonylurea drug for the treatment of type 2 diabetes mellitus (DM). Recent studies have suggested that glibenclamide reduced adverse neuroinflammation and improved behavioral outcomes following central nervous system (CNS) injury. We reviewed glibenclamide's anti-inflammatory effects: abundant evidences have shown that glibenclamide exerted an anti-inflammatory effect in respiratory, digestive, urological, cardiological, and CNS diseases, as well as in ischemia-reperfusion injury. Glibenclamide might block KATP channel, Sur1-Trpm4 channel, and NOD-like receptor pyrin domain containing 3 (NLRP3) inflammasome activation, decrease the production of proinflammatory mediators (TNF-α, IL-1β, and reactive oxygen species), and suppress the accumulation of inflammatory cells. Glibenclamide's anti-inflammation warrants further investigation.